Sedimentological and ichnological characterization of muddy storm related deposits: The upper Hauterivian ramp of the Agrio Formation in the Neuquén Basin, Argentina. (May 2018) - Comerio, Marcos; Fernández, Diana Elizabeth; Pazos, Pablo José
Abstract: The lowermost part of the Agua de la Mula Member (upper Hauterivian), Agrio Formation, was studied in distal depositional settings at four locations in the central Neuquén Basin. Detailed sedimentological and ichnological analysis combining field data and microfacies, using petrography, X-ray diffraction, and organic geochemical data allow to recognize two facies associations, representing proximal to distal facies of a mixed, carbonate-siliciclastic homoclinal outer ramp. The distal outer ramp facies association (FA-1) contains mudstones accumulated by suspension settling during periods of high productivity in the water column with calcareous microfossils as fecal pellets and organo-minerallic aggregates. Very thin (<5 mm thick) beds with local skeletal debris and subtle erosional features suggest storm-generated turbidite-like deposits related to bottom currents that interrupted this "low-energy" scenario. Conversely, the proximal outer ramp facies association (FA-2) is mainly composed of illite-rich floccules with terrigenous organic matter derived from the hinterland, probably transported by suspension in the way of benthic fluid mud. The partially bioturbated clay-bearing, silt-rich mudstones are organized into stacked successions of sharp-based, normally graded and very thin (<5 mm thick) beds indicative of erosive waning flows. In these mudstones, the preservation of parallel to curved ripple lamination indicates storm-driven bottom currents that transported mud as bed load into the proximal outer ramp. Some bioturbated mudstones with Phycosiphon incertum demonstrate a close relationship between event bed deposits and oxygenation pulses of the bottom waters by storm-influenced processes. Graphical abstract: Highlights: Mudstone microfacies in upper Hauterivian outer ramp settings. High content of primary organic products in the distal outer ramp. Illite-rich floccules dominate in the proximal outer ramp. Phycosiphon incertum related to tempestite-like deposits. Oxygenation pulses of the bottom waters by storm-influenced processes.